L’écriture cartographique de l’histoire en littérature de jeunesse - Sabrina Messing (Amnis)
As in all literature, children's literature has a marked geographic dimension found notably in the many maps it offers. Topographic or illustrated maps give not just geographic contents but also historic contents both in the textual elements (dates etc) and in the illustrations (portraits of historic characters amongst other). This spatialisation of history adds to the writing of history through children's literature. This leads us to question the status quo and changes in the cartographic slide in relation to the fictional text.